Profesionalitas Guru Pendidikan Agama Katolik Dalam Meningkatkan Kualitas Iman Siswa Di Kota Palangka Raya - Apprilianti Arzulia; Paulina Maria Ekasari Wahyuningrum; Silvester Adinuhgra (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This study aims to describe the professionalism of Catholic religious education teachers as a determining factor for the quality of the faith of students in the city of Palangka Raya. The quality of students' faith is considered important in the context of religious education, because it can shape the character and morals of students in depth. This research is a qualitative research with a descriptive method, the data source of the research was taken from 7 teachers spread across various public elementary schools and public junior high schools in Palangka Raya. This research was conducted in July 2023 in the city of Palangka Raya. The data collection technique used interviews. Data analysis techniques used the theory of Miles and Huberman, which consisted of 3 stages, namely data reduction, data presentation and drawing conclusions. The results of this study describe the professional competence of Catholic religious education teachers in shaping the quality of students' faith by using strategies that are given not only through theory in class but teachers also have creativity in creating learning that is able to achieve learning goals. The hope derived from the results of this study can be concluded that it is expected to provide valuable information to Catholic educational institutions in Palangka Raya to improve the competence and quality of religious education and to support the spiritual development of students holistically.